Analysis of wake surfing benefits using a fast unsteady vortex lattice method - Fleischmann, Dominique; Lone, Mudassir (AIAA, 2019)
The computer simulation framework Flexit is used to analyse the fuel economy benefit of aircraft wake surfing. Wake surfing involves multiple aircraft flying in close formation during cruise conditions to reduce overall induced drag and improve overall fuel efficiency. The aircraft fly in echelon such that the kinetic energy lost in vortices generated by the lead aircraft can be partially recovered by the following aircraft flying in regions of the wake where induced velocities have an upwardly directed vertical component. We build on recent theoretical and flight test work by developing a medium fidelity methodology using Flexit for predicting potential performance benefits of wake surfing. We present results from a specific systematic parametric study that corresponds to a series of recent flight tests with two C-17 transport aircraft to demonstrate the methodology and predict the fuel savings that can be obtained by different arrangements of aircraft in a wake surfing formation. The predictions are compared with the flight test data and the trends observed in our simulations agree with the trends of the full scale tests.